Introduction to AC machine design - Lipo, T. A.; IEEE Xplore (Online Service); Wiley (Hoboken, New Jersey : Wiley, 2017)
The only book on the market that emphasizes machine design beyond the basic principles of AC and DC machine behavior AC electrical machine design is a key skill set for developing competitive electric motors and generators for applications in industry, aerospace, and defense. This book presents a thorough treatment of AC machine design, starting from basic electromagnetic principles and continuing through the various design aspects of an induction machine. Introduction to AC Machine Design includes one chapter each on the design of permanent magnet machines, synchronous machines, and thermal design. It also offers a basic treatment of the use of finite elements to compute the magnetic field within a machine without interfering with the initial comprehension of the core subject matter. Based on the author's notes, as well as years of classroom instruction, Introduction to AC Machine Design: . Brings to light more advanced principles of machine design - not just the basic principles of AC and DC machine behavior. Introduces electrical machine design to neophytes while also being a resource for experienced designers. Fully examines AC machine design, beginning with basic electromagnetic principles. Covers the many facets of the induction machine design Introduction to AC Machine Design is an important text for graduate school students studying the design of electrical machinery, and it will be of great interest to manufacturers of electrical machinery.
Magnetic Circuits -- The MMF and Field Distribution of an AC Winding -- Main Flux Path Calculations Using Magnetic Circuits -- Use of Magnetic Circuits in Leakage Reactance Calculations -- Calculation of Induction Machine Losses -- Principles of Design -- Thermal Design -- Permanent Magnet Machines -- Electromagnetic Design of Synchronous Machines -- Finite-Element Solution of Magnetic Circuits -- Computation of Bar Current -- Fem Example.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web
Online resource; title from PDF title page (John Wiley, viewed October 11, 2017).
Keywords: Electric machinery -- Alternating current; Electronic books